2016
DOI: 10.3389/fphar.2016.00055
|View full text |Cite|
|
Sign up to set email alerts
|

Discoidin Domain Receptors: Potential Actors and Targets in Cancer

Abstract: The extracellular matrix critically controls cancer cell behavior by inducing several signaling pathways through cell membrane receptors. Besides conferring structural properties to tissues around the tumor, the extracellular matrix is able to regulate cell proliferation, survival, migration, and invasion. Among these receptors, the integrins family constitutes a major class of receptors that mediate cell interactions with extracellular matrix components. Twenty years ago, a new class of extracellular matrix r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 108 publications
1
90
0
Order By: Relevance
“…It is shown that the discoidin receptor, DDR1, facilitates chemoresistance via the NF-κβ pathway [98]. Given that discoidin receptors promote tumor progression independently, as well as through interactions with integrins, such as α 2 β 1 integrin [99], it will be worthwhile to investigate their role, together with that of integrins, in promoting chemoresistance.…”
Section: Ecm Mediates Treatment Resistancementioning
confidence: 99%
“…It is shown that the discoidin receptor, DDR1, facilitates chemoresistance via the NF-κβ pathway [98]. Given that discoidin receptors promote tumor progression independently, as well as through interactions with integrins, such as α 2 β 1 integrin [99], it will be worthwhile to investigate their role, together with that of integrins, in promoting chemoresistance.…”
Section: Ecm Mediates Treatment Resistancementioning
confidence: 99%
“…DDRs regulate important aspects of cellular processes including proliferation, migration, adhesion, and ECM remodeling by interacting with several types of collagen [6]. In several human cancers, such as breast cancer, lung cancer, and hepatocarcinoma, dysregulated DDRs have been observed to be related with tumor development [7].…”
Section: Introductionmentioning
confidence: 99%
“…To date, published studies of DDR1 in cancer have been limited to its action in tumor cells 20,21 . Using genetically engineered mice and syngeneic tumor models, we demonstrate the importance of host DDR1 in tumor growth, thus significantly extending the current understanding of DDR1 tumor-promoting function.…”
Section: Discussionmentioning
confidence: 99%
“…DDR1 is predominantly expressed in normal epithelial cells and its aberrant expression is associated with multiple solid cancer types. For these reasons, the current literature on DDR1 function in cancer biology has exclusively been focused on its activity in tumor cells [20][21][22] . However, comparative gene expression profiling shows that stromal DDR1 expression in invasive breast cancer is significantly elevated versus normal breast stroma 23 (6.4-fold, p= 1x10 -15 ), suggesting a possible DDR1 function in stromal cells during cancer progression.…”
Section: Introductionmentioning
confidence: 99%